Synopsis of Barra Jordan, 1904 (Coleoptera: Anthribidae) with description of a new species from Brazil with an updated key to the genus - Vilhena, Poliana De Mesquita; Lopes, Marcela Paes De Azevedo Machado; Mermudes, José Ricardo Miras (Zootaxa, 2025)
Barra tocantinensis Vilhena, Lopes & Mermudes sp. nov. (Anthribinae: Piesocorynini) is described from Serra do Lajeado Ecological Reserve (Fazenda Céu), a threatened biome in central-western Brazil. A key to the all known species of Barra is presented. New data on the distribution of the genus are provided.